Rancang Bangun Sistem Informasi Rekam Medis Untuk Klinik Menggunakan FatFree PHP Framework - imam isr isr; ubaidilah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2024)
Abstract - The Indonesian government has determined that by the end of 2023 all health service facilities in Indonesia must implement electronic medical records or RME. Electronic medical records using information technology in the form of information system applications. The medical record information system (SIRM) manages various data such as patient identity notes and documents, examinations, treatment, procedures and other services that have been provided to patients. SIRM is one of the most promising components in health information technology. To support this government program, researchers developed a medical record information system that can be used by health service managers in general. This information system carries the concept of a web-based application which provides ease of implementation and access by users. The system created includes recording patient data, registering health services by patients, recording medical records, and calculating service bills paid by patients.